Digital Technology-Based Learning Strategies in Junior High Schools: A Case Study at Muhammadiyah 3 Junior High School, Depok, Sleman - Puji Lestari, Esty; Martaningsih, Sri Tutur; Hasanah, Enung (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Digital education transformation often focuses solely on infrastructure without addressing managerial aspects and character values. This study aims to analyze digital technology-based learning strategies at SMP Muhammadiyah 3 Depok Sleman, a school that integrates the digital school concept with strengthening Islamic character. Using a qualitative case study design approach, data were collected through in-depth interviews, observations, and documentation of the principal, curriculum, and teachers. Data analysis was conducted with the help of ATLAS.ti 9 software to ensure objectivity and depth of theme categorization. The results show that the school's strategy rests on the integration of the TPACK (Technological Pedagogical Content Knowledge) framework packaged within the POAC (Planning, Organizing, Actuating, Controlling) management unique to Muhammadiyah. Key findings reveal that the success of digitalization lies not only in the availability of devices but also in the formation of a digital ecosystem that aligns with the school's religious identity. This study contributes to the digital school management model in faith-based educational institutions.